The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1108/ijbpa-06-2023-0082
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of space efficiency in Asian supertall towers

Hüseyin Emre Ilgın

Abstract: PurposeSupertall towers (300 m+) offer a viable solution to the increasing demand for housing and commercial space caused by rapid urban growth, migration from rural to urban areas and economic expansion in Asia. In this particular context, the efficient utilization of space becomes a crucial factor in the design process for Asian skyscrapers as they seek to address the changing socioeconomic landscape. This study will provide valuable guidance, especially to architectural and structural designers in the pursu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, in the context of constructing supertall buildings, a paradigm shift occurs, with outriggered frame systems assuming a commonplace role. This distinctive trend signifies a deliberate departure from conventional choices, highlighting the unique structural considerations that come into play when engineering exceptionally tall structures [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of constructing supertall buildings, a paradigm shift occurs, with outriggered frame systems assuming a commonplace role. This distinctive trend signifies a deliberate departure from conventional choices, highlighting the unique structural considerations that come into play when engineering exceptionally tall structures [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…Ilgın [29] conducted a thorough investigation into the spatial efficiency of 75 supertall buildings situated in Asia. The study's main findings can be outlined as follows: (a) the average spatial efficiency was 67.5%, with a range from 55% to 82%; (b) the mean ratio of core to gross floor area (GFA) was about 30%, varying between 14% and 38%.…”
Section: Literature Surveymentioning
confidence: 99%
“…The study found space efficiency ranging from 78% to 88%. Ilgın [25][26][27][34][35][36] investigated space efficiency in various types of skyscrapers, including office, residential, and mixed-use towers. Common findings across these studies included the frequent use of outriggered frame systems and a central core, and an inverse relationship between tower height and space efficiency.…”
Section: Introductionmentioning
confidence: 99%